STRATEGI ADAPTASI SISTEM PERTANIAN DAN LINGKUNGAN PERAIRAN DALAM MENGHADAPI DAMPAK PASCABANJIR BANDANG DAS KURANJI DI KECAMATAN KURANJI, KOTA PADANG - M. Amri; Budi Santosa; Siti Aisyah; Dicky Rustam; Murhenna Uzra (Smart Education, 2026)
Flash floods in the Kuranji Watershed area, Kuranji District, Padang City, have had a significant impact on the agricultural system, aquatic environment, and socio-economic conditions of the community. This study aims to analyze the condition of the agricultural system and aquatic environment after the flash flood, identify internal and external factors, and formulate adaptation strategies based on a SWOT analysis. The study used a mixed methods approach with a survey method through observation, interviews, and questionnaires distributed to 100 respondents determined using the Slovin formula. Data analysis was carried out using the IFAS matrix, EFAS, and SWOT quadrants. The results showed that flash floods caused increased damage to agricultural land, disruption of irrigation systems, decreased agricultural productivity, high river sedimentation, and decreased quality of the aquatic environment. The main strengths include the availability of water resources and community experience in the agricultural sector, while the main weaknesses are high river sedimentation and damage to the irrigation system. Opportunities come from government support and watershed rehabilitation programs, while the main threats are high rainfall and recurring floods. The results of the SWOT analysis indicate that the strategy is positioned in Quadrant III (turnaround strategy). Recommended priority strategies include watershed rehabilitation, river normalization, sedimentation control, irrigation system improvement, and strengthening community capacity in disaster mitigation.